Method development for the quantitative determination of captopril from Caco-2 cell monolayers by using LC-MS/MS - Logoyda, L.; Piponski, M.; Kovalenko, S.; Dutchak, O.; Denefil, O.; Soroka, Y.; Pidruchna, S.; Popovych, D.; Susla, O.; Коваленко, Сергій Іванович (My University, 2021)
Caco-2 cells are a human colon epithelial cancer cell line used as a model of human intestinal absorption of drugs and other compounds. Although compounds were used in the original Caco-2 cells monolayer assays, compounds have been replaced in most laboratories by the use of liquid chromatography-mass spectrometry (LC-MS) and LC-tandem mass spectrometry (LC-MS/MS). Mass spectrometry not only eliminates the need for compounds, but permits the simultaneous measurement of multiple compounds. The measurement of multiple compounds per assay reduces the number of incubations that need to be carried out, thereby increasing the throughput of the experiments. Furthermore, LC-MS and LC-MS-MS add another dimension to Caco-2 assays by facilitating the investigation of the metabolism of compounds by Caco-2 cells. A simple, rapid LC-MS/MS method has been developed for determination of captopril from confluent Caco-2 monolayers and from aqueous solution. Materials and methods. Chromatography was achieved on Discovery C18, 50 × 2.1 mm, 5 μm column. Samples were chromatographed in a gradient mode (eluent A (acetonitrile – water – formic acid, 5 : 95 : 0.1 v/v), eluent B (acetonitrile – formic acid, 100 : 0.1 v/v)). The initial content of the eluent B is 0%, which increases linearly by 1.0 min to 100% and to 1.01 min returns to the initial 0%. The mobile phase was delivered at a flow rate of 0.4 mL/min into the mass spectrometer ESI chamber. The sample volume was 5 μl. Results. Under these conditions, captopril was eluted at 1.42 min. A linear response function was established at 2 – 200 ng/mL. The regression equation for the analysis was y =0.0187x+0.000248 with coefficient of correction (r2 ) = 0.9993. According to the Caco-2 test results, captopril showed low permeability. It should be noted that the recovery value is 103.20%. The within-run coefficients of variation ranged between 0.321% and 0.541%. The within-run percentages of nominal concentrations ranged between 99.13% and 101.12%. The between-run coefficients of variation ranged between 0.314% and 0.663%. The between-run percentages of nominal concentrations ranged between 99.17% and 101.03%.The assay values on both the occasions (intra- and inter-day) were found to be within the accepted limits. Conclusion. From results of analysis, it can be concluded that developed method is simple and rapid for determination of captopril from confluent Caco-2 monolayers and from aqueous solution. Acquired results demonstrate that proposed strategy can be effortlessly and advantageously applied for examination of captopril from Caco-2 cell monolayers.
Keywords: Caco-2 cells; Captopril; LC-MS/MS; Permeability; Recovery